2017
DOI: 10.1038/s41598-017-03870-y
|View full text |Cite
|
Sign up to set email alerts
|

Anger provocation in violent offenders leads to emotion dysregulation

Abstract: Anger and anger regulation problems that result in aggressive behaviour pose a serious problem for society. In this study we investigated differences in brain responses during anger provocation or anger engagement, as well as anger regulation or distraction from anger, and compared 16 male violent offenders to 18 non-offender controls. During an fMRI adapted provocation and regulation task participants were presented with angry, happy and neutral scenarios. Prior research on violent offenders indicates that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The present results conversely imply that the use of distraction strategies in the presence of threat or provocation might help in curbing aggressive impulses (Lievaart, Huijding, van der Veen, Hovens, & Franken, 2017;Vasquez et al, 2013). Indeed, violent offenders show reduced amygdala engagement when distracting themselves from imagined angerinducing situations, compared with when they focus on their feelings of anger (Tonnaer, Siep, van Zutphen, Arntz, & Cima, 2017). These effects were confined to the BLA and did not extend into the CMA.…”
Section: Attentional Biases To Antisocial Information and Neurobiolsupporting
confidence: 48%
See 1 more Smart Citation
“…The present results conversely imply that the use of distraction strategies in the presence of threat or provocation might help in curbing aggressive impulses (Lievaart, Huijding, van der Veen, Hovens, & Franken, 2017;Vasquez et al, 2013). Indeed, violent offenders show reduced amygdala engagement when distracting themselves from imagined angerinducing situations, compared with when they focus on their feelings of anger (Tonnaer, Siep, van Zutphen, Arntz, & Cima, 2017). These effects were confined to the BLA and did not extend into the CMA.…”
Section: Attentional Biases To Antisocial Information and Neurobiolsupporting
confidence: 48%
“…Subjects who show stronger interference caused by antisocial cues might thus be more likely to ruminate on the opponent's anger displays and/or to perceive them as more intense. Indeed, violent offenders show reduced amygdala engagement when distracting themselves from imagined angerinducing situations, compared with when they focus on their feelings of anger (Tonnaer, Siep, van Zutphen, Arntz, & Cima, 2017). In line with this formulation, direct electrophysiological recordings showed that quick amygdala responses to videos depicting interpersonal harm predict intentionality attribution (Hesse et al, 2016).…”
Section: Attentional Biases To Antisocial Information and Neurobiolmentioning
confidence: 95%
“…Although very speculative, one could argue that the effects of anger venting in the FPO group supports the catharsis theory. Recent functional magnetic resonance imaging (fMRI) research on anger provocation and regulation showed regulation difficulties in violent offenders, with an increased need to regulate during anger provocation and regulation difficulties when explicitly instructed to distract (Tonnaer et al, 2017). The constant effort required for violent offenders to regulate anger might exhaust the necessary cognitive resources, resulting in a risk for self-control failure.…”
Section: Discussionmentioning
confidence: 99%
“…Scores were calculated by summing the statement values within the dimension category for all anger segments. Research shows that ATSS is able to trigger anger- (Tonnaer, Siep, van Zutphen, Arntz, & Cima, 2017) and aggression-related cognitions (Barbour, Eckhardt, Davison, & Kassinove, 1998;. For the current study, the anger dimension category scores were used to assess ATSS provocation (Tonnaer et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study we focus on data of the resting-state scans pre and post the experimental paradigm, testing for brain differences in functional connectivity as previous research has shown that pre and post resting state connectivity can be altered by fMRI task performance (Tung et al, 2013). FMRI data results on the experimental task, along with a more detailed description of the paradigm, its instructions and the immediate effects are reported elsewhere (Tonnaer et al, 2017). In this task participants were presented with audio audiotaped (anger, neutral and happy) stories, each within an Engagement condition instructing participants to focus on one's emotional feeling, and a Distraction condition instructing participants to distract themselves from the presented stories during fMRI scanning.…”
Section: Methodsmentioning
confidence: 99%